2022
DOI: 10.1038/s41591-022-01736-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling comparative cost-effectiveness of SARS-CoV-2 vaccine dose fractionation in India

Abstract: Given global Coronavirus Disease 2019 (COVID-19) vaccine shortages and inequity of vaccine distributions, fractionation of vaccine doses might be an effective strategy for reducing public health and economic burden, notwithstanding the emergence of new variants of concern. In this study, we developed a multi-scale model incorporating population-level transmission and individual-level vaccination to estimate the costs of hospitalization and vaccination and the economic benefits of reducing COVID-19 deaths due t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…The fail-safe number was seven, indicating seven studies or interventions with negative results could change the current results. Of the remaining 15 studies on COVID-19 vaccination, 12 concluded that COVID-19 vaccinations were cost-effective [ 87 - 98 ] and two suggested that parts of the vaccination strategies were optimal [ 99 , 100 ]. Only one study reported the conclusion depended on the primary outcome of interest [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fail-safe number was seven, indicating seven studies or interventions with negative results could change the current results. Of the remaining 15 studies on COVID-19 vaccination, 12 concluded that COVID-19 vaccinations were cost-effective [ 87 - 98 ] and two suggested that parts of the vaccination strategies were optimal [ 99 , 100 ]. Only one study reported the conclusion depended on the primary outcome of interest [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the younger population with a tendency for higher contact rates, vaccination with relatively lower efficacy and great coverage could reduce the probability of transmission and would be cost-effective [ 101 , 111 ]. Du et al [ 99 ] suggested that dose-sparing strategies could save a large number of lives, even with the emergence of new variants with higher transmissibility in India.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vaccination campaigns are really important in order to induce herd immunity, which could mitigate the threat of COVID-19 pandemic. Hence, rapid production and supply of various vaccines are crucial [103]. Besides, mixing different vaccine to achieve an elevated level of immunity can also be an approach to overcome the shortage of vaccines in poor countries.…”
Section: Discussionmentioning
confidence: 99%
“…Only one simple utility function was considered in this work. This could be made more complex by including dose–cost relationships or modelling dose–response curves for multiple different efficacy or toxicity responses [ 11 , 60 , 64 ]. Creating a meaningful utility function is non-trivial [ 65 , 66 ] and is key to effective optimisation.…”
Section: Discussionmentioning
confidence: 99%